IJCM_311A: Epidemiological profile of tuberculosis cases at an urban slum in a metropolitan city a cross sectional study - Pinto Tanvi; Chavan Y.B; Singh Vijaykumar (Wolters Kluwer Medknow Publications, 2024)
Background: The WHO Global Tuberculosis Programme works towards the goal of a world free of TB, with zero deaths, disease and suffering due to the disease. Tuberculosis (TB) is a preventable and usually curable disease. Yet in 2022, TB was the worlds second leading cause of death from a single infectious agent, after coronavirus disease (COVID-19). The reported global number of people newly diagnosed with TB was 7.5 million in 2022; this is the highest number since WHO began global TB monitoring in 1995. Around 87% of new TB cases occurred in the 30 high TB burden countries, with more than two-thirds of the global total in Bangladesh, China, Democratic Republic of the Congo, India, Indonesia, Nigeria, Pakistan and the Philippines. Objective: To study the epidemiological profile of tuberculosis cases in an urban slum of Mumbai. Methodology: A retrospective record-based analysis of secondary data on tuberculosis (pulmonary and extrapulmonary) reported on the NIKSHAY portal between January to December 2022 at an urban health training center in an urban slum in Mumbai. Results: The total number of drug sensitive TB cases reported in 2022 was 519. Males constituted 42% and females 58%. The most common age group affected was 20-29 years. Pulmonary cases comprised 66.9% of the cases. The total number of Drug resistant TB cases reported were 75, 53 were pulmonary & 22 were extrapulmonary. Conclusion: In contrast to Male predominance (52.26%) of cases in Maharashtra, the urban slum had 42% males affected. India grapples with multiple challenges in combatting tuberculosis (TB), marked by a high disease burden, diagnostic delays, drug resistance, and socioeconomic barriers. While significant strides have been made through programs like the National Tuberculosis Elimination Program, the path to eradication demands continued efforts.